Estimasi Biaya Pembuatan Perangkat Lunak Sistem Informasi Akademik (Studi Kasus Solusi Sistem Informasi Stikom Surabaya) - Annisa, Faiqotul; Widodo, Arifin Puji; Arnandy, Didiet Anindita (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Pusat Kerja Sama Solusi Sistem Informasi (PKS-SSI) Stikom Surabaya didn’t have calculation standard for making cost estimation, effort calculation and optimal work schedule in the making of SIPERTI AAK. Until now PKS-SSI making cost estimation based on past experience which made approximately 10% of the project going off-scheduleIn this research the calculation solution created to assist PKS-SSI in calculating SIPERTI AAK’s development cost estimation is using Function Point Analysis (FPA) method. The FPA method can generate effort value and optimal work schedule for the development of SIPERTI AAK.After this research had been conducted it is found that the total function point is 524,52. The effort distribution found at 63,65% for software development, 14,97% for on going activity, and 21,38% for quality assurance. For best in class software organization the effort is 124,99 person-month with 15 month work schedule and Rp. 941.455.183 software development cost. For average software organization the effort is 182,37 person-month with 17,01 month work schedule and Rp. 723.801.655 software development cost. And last for worst in class software organization the effort is 321,45 person-month with 20,55 month work schedule and Rp. 458.754.054 software development cost. Keywords: Software, Cost Estimation, Function Point Analysis